The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/amt-8-4735-2015
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution measurements from the airborne Atmospheric Nitrogen Dioxide Imager (ANDI)

Abstract: Abstract. Nitrogen dioxide is both a primary pollutant with direct health effects and a key precursor of the secondary pollutant ozone. This paper reports on the development, characterisation and test flight of the Atmospheric Nitrogen Dioxide Imager (ANDI) remote sensing system. The ANDI system includes an imaging UV/Vis grating spectrometer able to capture scattered sunlight spectra for the determination of tropospheric nitrogen dioxide (NO 2 ) concentrations by way of DOAS slant column density and vertical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 37 publications
5
27
0
Order By: Relevance
“…These types of measurements from aircraft are relatively new, with push broom NO 2 airborne 2-D measurements reported recently over the Highveld region of South Africa (Heue et al, 2008), Zurich, Switzerland (Popp et al, 2012), northwest Germany (Schönhardt et al, 2015) and Leicester, United Kingdom (Lawrence et al, 2015). General et al (2014) have also recently reported airborne 2-D observations of volcanic BrO and SO 2 over Mt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of measurements from aircraft are relatively new, with push broom NO 2 airborne 2-D measurements reported recently over the Highveld region of South Africa (Heue et al, 2008), Zurich, Switzerland (Popp et al, 2012), northwest Germany (Schönhardt et al, 2015) and Leicester, United Kingdom (Lawrence et al, 2015). General et al (2014) have also recently reported airborne 2-D observations of volcanic BrO and SO 2 over Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties in surface reflectivity, the vertical distribution of aerosols relative to NO 2 and trace gas vertical profiles generally dominate air mass factor uncertainties for cloud-free NO 2 data. Lawrence et al (2015) estimated an AMF uncertainty of ∼ 8 % in remotely sensed NO 2 from an airborne mission over Leicester, United Kingdom, primarily resulting from uncertainties in the surface albedo and NO 2 profile shape.…”
Section: Air Mass Factor and Model Uncertaintiesmentioning
confidence: 99%
“…Only a few recent studies report on the high-resolution 2-D spatial mapping of the NO 2 horizontal distribution from an airborne platform. The discussed hyperspectral imaging systems are based on a whiskbroom Liu et al, 2015) or pushbroom set-up (Heue et al, 2008;Popp et al, 2012;General et al, 2014;Lawrence et al, 2015;Schönhardt et al, 2015;Meier et al, 2016;Nowlan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Etna, Italy. Urban NO 2 distributions were measured by Popp et al (2012) above the city of Zürich, Switzerland, and by Lawrence et al (2015) above the city of Leicester, England.…”
mentioning
confidence: 99%